INDUSTRIAL 4.0 APPLICATION IN INDONESIAN HOSPITAL: A CASE STUDY - Wisudawati, Tri; Worldailmi , Elanjati (International Journal of Psychosocial Rehabilitation, 2020)
The industrial revolution of 4.0 drives technological innovation in terms of production and services to provide fundamental disruption or change to people’s lives. It also presents a challenge for the industrial world, including the hospital industry. Hospital management supports to make changes in all areas to respond to the future needs of hospital customers. This research is a case study discussing the Indonesian hospital in Yogyakarta. The research method is a descriptive analysis that discusses the activities and processes at the Indonesian hospital by looking at the perspectives of several references and then evaluating them. The data are obtained from respondents who have several times a reference and experience of the service system. This research reveals that the application of industry 4.0 in hospitals in Yogyakarta is expected to be used as a reference for other hospitals in Indonesia, especially in terms of the service system.